Pregnancy exposure to atmospheric pollution and meteorological conditions and placental DNA methylation. (September 2018) - Abraham, Emilie; Rousseaux, Sophie; Agier, Lydiane; Giorgis-Allemand, Lise; Tost, Jörg; Galineau, Julien; Hulin, Agnès; Siroux, Valérie; Vaiman, Daniel; Charles, Marie-Aline; Heude, Barbara; Forhan, Anne; et al.
Abstract: Background: Air pollution exposure represents a major health threat to the developing foetus. DNA methylation is one of the most well-known molecular determinants of the epigenetic status of cells. Blood DNA methylation has been proven sensitive to air pollutants, but the molecular impact of air pollution on new-borns has so far received little attention. Objectives: We investigated whether nitrogen dioxide (NO2 ), particulate matter (PM10 ), temperature and humidity during pregnancy are associated with differences in placental DNA methylation levels. Methods: Whole-genome DNA-methylation was measured using the Illumina's Infinium HumanMethylation450 BeadChip in the placenta of 668 newborns from the EDEN cohort. We designed an original strategy using a priori biological information to focus on candidate genes with a specific expression pattern in placenta (active or silent) combined with an agnostic epigenome-wide association study (EWAS). We used robust linear regression to identify CpGs and differentially methylated regions (DMR) associated with each exposure during short- and long-term time-windows. Results: The candidate genes approach identified nine CpGs mapping to 9 genes associated with prenatal NO2 and PM10 exposure [false discovery rate (FDR) p < 0.05]. Among these, the methylation level of 2 CpGs located in ADORA2B remained significantly associated with NO2 exposure during the 2nd trimester and whole pregnancy in the EWAS (FDR p < 0.05). EWAS further revealed associations between the environmental exposures under study and variations of DNA methylation of 4 other CpGs. We further identified 27 DMRs significantly (FDR p < 0.05) associated with air pollutants exposure and 13 DMRs with meteorological conditions. Conclusions: The methylation of ADORA2B, a gene whose expression was previously associated with hypoxia and pre-eclampsia, was consistently found here sensitive to atmospheric pollutants. In addition, air pollutants were associated to DMRs pointing towards genes previously implicated in preeclampsia, hypertensive and metabolic disorders. These findings demonstrate that air pollutants exposure at levels commonly experienced in the European population are associated with placental gene methylation and provide some mechanistic insight into some of the reported effects of air pollutants on preeclampsia. Highlights: DNA methylation was measured in 668 placentas using the HumanMethylation450 BeadChip. We used an original strategy combining a concept-driven and agnostic approaches. Methylation of Alu or LINE-1 sequences was mainly not associated with air pollutants. Pregnancy NO2 exposure was associated with lower ADORA2B methylation in multiple CpGs. Highlighted genes were related to preeclampsia, hypertensive and metabolic disorders.